Ethnobotanical survey of plants used in the management of hypertension in Ibadan north local government area of Oyo state, Nigeria (2019)
Background: Among diseases that affect humans, the non-communicable diseases (NCDs) are quite a number of which hypertension is a leading member of the group and a leading contributory cause of death worldwide. Objective: To identify and document medicinal plants used in ethno-medical management of hypertension in selected communities within Ibadan metropolis. This is with the aim of contributing to a database of plants for future systematic biological and chemical evaluation for possible templates of anti-hypertensive agents and drug leads. Materials and methods: An inventory of plant species/natural remedies used in folk medicine to manage hypertension in Ibadan North Local Government Area of Oyo State was undertaken. Interviews using semi-structured questionnaires and open-ended conversations were conducted among one hundred and seventy-six (176) respondents aged 30 years and above to obtain relevant information. Results: A total of one hundred and one (101) plants belonging to fifty-four (54) families were identified of which the highest number of plants mentioned belong to family Compositae. The usage profiles of the plants were quantified by the quotation frequency/ mention index. Conclusion: It was observed that Ibadan is a rich source of plants indicated in management of hypertension. More scientific work especially biological studies are needed to ascertain the efficacy, toxicity, safety and appropriate dosage regimen of these ethno-medicinal remedies.